Expansion type anti-laser coating and preparation method thereof
By designing a multi-layer structure expansion anti-laser coating, using components such as carbohydrates and sugars, combined with sandblasting and multi-layer coating technology, the instantaneous thermal action problem caused by high-power density lasers is solved, and a higher level of energy has been achieved With a lighter coating, it is suitable for high-power laser environments.
Patent Information
- Application Number
- CN202411443998.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2024-12-13
AI Technical Summary
The existing anti-laser coatings are difficult to effectively resist instantaneous thermal effects when facing high-power density lasers, resulting in substrate damage, and are large in weight and difficult to expand thickness to improve tolerance time.
Using a multi-layer structure, the expansion anti-laser coating includes carbohydrate powders, pyranose compounds, hydroxyl-containing sugars and their derivatives, sodium bicarbonate/borax and deionized water/polymer solutions, through special Components and ratio design form a coating with a body density of no more than 2.6g/cm3, with a thickness of 0.1mm for each coating. The surface roughness of the substrate is increased by sandblasting, and the thickness requirement is achieved through multi-layer cross-coating.
The coating can withstand 1064nm continuous laser power density 500W/cm2 Gaussian spot duration 40s or 2000W/cm2 Gaussian spot duration 10s. The center temperature on the back of the substrate is lower than 170℃ or 230℃, effectively reducing the transmission of laser energy to the substrate and extending the Tolerance time.
Smart Images

Figure CN119119806A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of laser coatings, and in particular to an expansion type anti-laser coating and a preparation method thereof. Background Art
[0002] Laser weapons are gradually maturing, posing a new threat to aircraft. Traditional aircraft surface materials such as topcoat, protective paint, skin, absorbing coating, absorbing honeycomb and other materials cannot withstand the strong laser irradiation of laser weapons. It is necessary to use anti-laser reinforcement technology to improve the laser damage threshold of the above materials and structures and extend the tolerance time under strong laser irradiation.
[0003] Typical laser-resistant reinforcement technologies can be roughly divided into two categories. One is ceramic coatings with ceramic as the typical material and plasma spraying as the typical preparation process, such as ZrB2 / SiC coatings, which can withstand 1064nm continuous laser power density of 500W / cm 2 The diameter of the 1cm spot lasts for 30 seconds. At this time, the coating is ablated and the substrate is not damaged. This type of anti-laser reinforcement technology mainly uses the inherent high temperature resistance of ceramics combined with the increase in reflectivity caused by the melting of the surface when the strong laser irradiates the coating to resist the instantaneous strong heat of the laser. This type of coating is heavy and usually used once. The other type is a composite coating with boron phenolic resin as the typical resin matrix and modified with inorganic fillers. This type of coating can withstand a 1064nm continuous laser power density of 500W / cm 2 The spot diameter is 1cm and the duration is 15s. This type of coating resists laser irradiation mainly based on the ablation mechanism. The modified resin coating is ablated under the strong heat of laser irradiation, and the internal chemical bonds are broken to form residual carbon. The instantaneous high heat caused by the laser acting on the coating is partially dissipated through the coupling effect of carbon heat conduction and infrared emission.
[0004] As laser weapons mature, their power density at the target has far exceeded 500W / cm 2 It is difficult to further increase the thickness of the above two coatings to resist laser weapons, and it is necessary to develop new anti-laser reinforcement technology.
[0005] Therefore, the inventor provides an expansion type anti-laser coating and a preparation method thereof. Summary of the invention
[0006] (1) Technical issues to be solved
[0007] The embodiment of the present invention provides an expansion type anti-laser coating and a preparation method thereof, which solves the technical problem of how to eliminate the instantaneous heat effect caused by high power density laser.
[0008] (2) Technical solution
[0009] The first aspect of the present invention provides an expandable anti-laser coating having a multilayer structure, each coating comprising carbohydrate powder, pyranose compounds, hydroxyl-containing sugars and derivatives thereof, sodium bicarbonate / borax and deionized water / polymer solution; wherein the mass proportion of the carbohydrate powder is 30-35%, the total mass proportion of the pyranose compounds, hydroxyl-containing sugars and derivatives thereof is 20-35%, and the mass proportion of the sodium bicarbonate / borax is 12-18%.
[0010] Furthermore, the thickness of each coating layer is 0.1 mm.
[0011] Furthermore, the pyranose compound is α-D-pyranose glucose.
[0012] Furthermore, the hydroxyl-containing sugar and its derivatives are sucrose.
[0013] Furthermore, the carbohydrate powder is flour, including at least one of wheat flour, corn flour and potato flour.
[0014] Furthermore, the bulk density of the coating is not greater than 2.6 g / cm 3 .
[0015] Furthermore, the mass ratio of the carbohydrate powder, the pyranose compound, the hydroxyl-containing sugar and its derivatives, the sodium bicarbonate / borax and the deionized water / polymer solution is 2:1:1:1:(1-5).
[0016] A second aspect of the present invention provides a method for preparing the above-mentioned expansion type anti-laser coating, comprising the following steps:
[0017] Sandblast the substrate to increase its surface roughness;
[0018] Carbohydrate powder, pyranose compounds, hydroxyl-containing sugars and their derivatives, polyvinyl alcohol / borax and deionized water / polymer solution are mixed according to a set mass ratio, stirred evenly, and a viscous paste is formed;
[0019] The viscous paste slurry is evenly applied to the surface of the substrate along a preset direction of the substrate, and dried after reaching a first preset thickness;
[0020] Apply a second layer perpendicular to the first coating direction and dry after reaching a second preset thickness;
[0021] Repeat the above steps to apply the anti-laser coating vertically and crosswise until the thickness requirement is met.
[0022] Furthermore, the first preset thickness is the same as the second preset thickness.
[0023] Furthermore, the drying time is 0.5 to 1 hour.
[0024] (3) Beneficial effects
[0025] In summary, the present invention adopts a laser-resistant coating designed by special components and ratios, and the coating can withstand a 1064nm continuous laser power density of 500W / cm 2 Gaussian spot duration 40s, or 1064nm continuous laser power density 2000W / cm 2 Gaussian spot duration 10s, substrate back center temperature below 170°C, or 1064nm continuous laser power density 2000W / cm 2 The Gaussian spot duration is 15s, and the center temperature of the back side of the substrate is lower than 230℃. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments of the present invention are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0027] Figure 1 It is a schematic structural diagram of an expansion type anti-laser coating provided by an embodiment of the present invention;
[0028] Figure 2 It is a schematic flow chart of a method for preparing an expansion type anti-laser coating provided in an embodiment of the present invention.
[0029] In the figure:
[0030] 1-substrate; 2-thermal expansion layer. DETAILED DESCRIPTION
[0031] The following detailed description of the embodiments of the present invention is provided in conjunction with the accompanying drawings and examples. The following detailed description of the embodiments and the accompanying drawings are used to illustrate the principles of the present invention, but cannot be used to limit the scope of the present invention, that is, the present invention is not limited to the described embodiments.
[0032] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0033] In the description of the present invention, it should be understood that the terms "upper", "lower", "front", "rear", etc. indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, or are the orientations or positional relationships in which the products of the present invention are conventionally placed when in use, or are the orientations or positional relationships conventionally understood by those skilled in the art. These are merely for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present invention.
[0034] Figure 1 is a schematic diagram of the structure of an expansion type anti-laser coating provided by an embodiment of the present invention, see Figure 1 The coating has a multi-layer structure, and each coating includes carbohydrate powder, pyranose compounds, hydroxyl-containing sugars and their derivatives, sodium bicarbonate / borax and deionized water / polymer solution; among them, the mass proportion of carbohydrate powder is 30-35%, the mass proportion of pyranose compounds, hydroxyl-containing sugars and their derivatives is 20-35%, and the mass proportion of sodium bicarbonate / borax is 12-18%.
[0035] In the above embodiment, when 10 2 W / cm 2 The above high-power density laser irradiates the surface of the thermal expansion layer 2. The laser deposits heat at the skin depth of the thermal expansion layer 2 to cause the thermal expansion layer 2 to expand. The deposited heat then causes the thermal expansion layer 2 to carbonize. The deposited heat is then conducted to the periphery of the light spot and emitted in an infrared manner, and the laser energy is reduced again until all the laser energy is eliminated, thereby reducing the heat conducted to the substrate 1, avoiding thermal-mechanical coupling damage to the substrate 1, and achieving the protection goal.
[0036] The thickness of each coating is 0.1 mm. The pyranose compound is α-D-pyranose glucose, the hydroxyl-containing sugar and its derivatives are sucrose, and the carbohydrate powder is flour, including at least one of wheat flour, corn flour and potato flour. The bulk density of the coating is not more than 2.6 g / cm 3 .
[0037] Furthermore, the mass ratio of carbohydrate powder, pyranose compound, hydroxyl-containing sugar and its derivatives, sodium bicarbonate / borax and deionized water / polymer solution is 2:1:1:1:(1-5).
[0038] Figure 2 is a schematic diagram of a method for preparing an expansion type anti-laser coating according to an embodiment of the present invention, see Figure 2 , the method may include the following steps:
[0039] S100, sandblasting the substrate to increase its surface roughness;
[0040] S200, mixing carbohydrate powder, pyranose compounds, hydroxyl-containing sugars and their derivatives, polyvinyl alcohol / borax and deionized water / polymer solution according to a set mass ratio, stirring evenly to form a viscous paste slurry;
[0041] S300, evenly coating the viscous paste slurry on the surface of the substrate along a preset direction of the substrate, and drying it after reaching a first preset thickness;
[0042] S400, applying a second layer in a direction perpendicular to the first coating direction, and drying after reaching a second preset thickness;
[0043] S500, repeat the above steps to vertically cross-coat the anti-laser coating until the thickness requirement is met.
[0044] Furthermore, the first preset thickness is the same as the second preset thickness.
[0045] Furthermore, the drying time is 0.5 to 1 hour.
[0046] Example 1 :
[0047] 1. Sandblast the substrate to increase its surface roughness;
[0048] 2. Mix wheat flour, α-D-pyranose glucose, sucrose, borax and deionized water in a volume ratio of 2:1:1:1:1.25 and stir evenly to form a viscous paste;
[0049] 3. Brush or spray the slurry evenly on the surface of the substrate along a certain direction of the substrate to a thickness of about 0.1 mm, and dry it for 0.5 hours;
[0050] 4. Brush or spray the second layer vertically in the direction of the first brushing to a thickness of about 0.1mm and let it dry for 0.5h;
[0051] 5. Repeat the above steps, brush or spray the anti-laser coating vertically and crosswise until the thickness meets the requirements.
[0052] Anti-laser effect: The coating can withstand 1064nm continuous laser power density of 500W / cm 2 Gaussian spot duration 40s, or 1064nm continuous laser power density 2000W / cm 2 Gaussian spot duration 10s, substrate back center temperature below 170°C, or 1064nm continuous laser power density 2000W / cm 2 The Gaussian spot duration is 15s, and the center temperature of the back side of the substrate is lower than 230℃.
[0053] Weight reduction effect: The coating body density is not more than 2.6g / cm 3 .
[0054] Example 2 : Instructions: Borax can be replaced with sodium bicarbonate
[0055] 1. Sandblast the substrate to increase its surface roughness;
[0056] 2. Mix flour, α-D-pyranose glucose, sucrose, sodium bicarbonate and deionized water in a volume ratio of 2:1:1:1:3 and stir evenly to form a viscous paste;
[0057] 3. Brush or spray the slurry evenly on the surface of the substrate along a certain direction of the substrate to a thickness of about 0.1 mm and dry it for 1 hour;
[0058] 4. Brush or spray the second layer vertically in the direction of the first brushing to a thickness of about 0.1mm and let it dry for 0.5h; 5. Repeat the above steps, brush or spray the anti-laser coating vertically and crosswise until the thickness meets the requirements.
[0059] Anti-laser effect: The coating can withstand 1064nm continuous laser power density of 500W / cm 2 Gaussian spot duration 40s, or 1064nm continuous laser power density 2000W / cm 2 Gaussian spot duration 10s, substrate back center temperature below 200℃, or 1064nm continuous laser power density 2000W / cm 2 The Gaussian spot duration is 15s, and the center temperature of the back side of the substrate is lower than 270℃.
[0060] Weight reduction effect: The coating body density is not more than 2.6g / cm 3 .
[0061] Example 3 : Indicates that changing the coating method has no effect on coating performance
[0062] 1. Sandblast the substrate to increase its surface roughness;
[0063] 2. Mix flour, α-D-pyranose glucose, sucrose, borax and deionized water in a volume ratio of 2:1:1:1:1.25 and stir evenly to form a viscous paste;
[0064] 3. Brush or spray the slurry evenly on the surface of the substrate along a certain direction of the substrate to a thickness of about 0.1 mm, and dry it for 0.5 hours;
[0065] 4. Brush or spray the second layer at 45 degrees along the direction of the first brushing to a thickness of about 0.1mm and let it dry for 0.5h;
[0066] 5. Brush or spray the third layer at 90 degrees along the direction of the second brushing to a thickness of about 0.1mm and let it dry for 0.5h;
[0067] 6. Brush or spray the fourth layer at 45 degrees along the three-brush direction to a thickness of about 0.1mm and let it dry for 0.5h;
[0068] 7. Repeat the above steps to vertically cross-brush or spray the anti-laser coating until the thickness meets the requirements.
[0069] Anti-laser effect: The coating can withstand 1064nm continuous laser power density of 500W / cm 2 Gaussian spot duration 40s, or 1064nm continuous laser power density 2000W / cm 2 Gaussian spot duration 10s, substrate back center temperature below 170°C, or 1064nm continuous laser power density 2000W / cm 2 The Gaussian spot duration is 15s, and the center temperature of the back side of the substrate is lower than 230℃.
[0070] Weight reduction effect: The coating body density is not more than 2.6g / cm 3 .
[0071] Example 4 :Deionized water can be replaced by other liquid polymers
[0072] 1. Sandblast the substrate to increase its surface roughness;
[0073] 2. Mix flour, α-D-pyranose glucose, sucrose, borax and polyurethane in a volume ratio of 2:1:1:1:5 and stir evenly to form a viscous paste;
[0074] 3. Brush or spray the slurry evenly on the surface of the substrate along a certain direction of the substrate to a thickness of about 0.1 mm, and dry it for 0.5 hours;
[0075] 4. Brush or spray the second layer at 45 degrees along the direction of the first brushing to a thickness of about 0.1mm and let it dry for 0.5h;
[0076] 5. Brush or spray the third layer at 90 degrees along the direction of the second brushing to a thickness of about 0.1mm and let it dry for 0.5h;
[0077] 6. Brush or spray the fourth layer at 45 degrees along the three-brush direction to a thickness of about 0.1mm and let it dry for 0.5h;
[0078] 7. Repeat the above steps to vertically cross-brush or spray the anti-laser coating until the thickness meets the requirements.
[0079] Anti-laser effect: The coating can withstand 1064nm continuous laser power density of 500W / cm 2 Gaussian spot duration 40s, or 1064nm continuous laser power density 2000W / cm2 Gaussian spot duration 10s, substrate back center temperature below 250°C, or 1064nm continuous laser power density 2000W / cm 2 The Gaussian spot duration is 15s, and the center temperature of the back side of the substrate is lower than 300℃.
[0080] Weight reduction effect: The coating body density is not more than 2.6g / cm 3 .
[0081] It should be clear that the various embodiments in this specification are described in a progressive manner, and the same or similar parts between the various embodiments can be referred to each other, and each embodiment focuses on the differences from other embodiments. The present invention is not limited to the specific steps and structures described above and shown in the figures. In addition, for the sake of brevity, a detailed description of known methods and technologies is omitted here.
[0082] The above are only embodiments of the present application and are not limited to the present application. For those skilled in the art, the present application may have various changes and variations without departing from the scope of the present invention. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present application should be included in the scope of the claims of the present application.
Claims
1. An expansion type anti-laser coating, characterized in that: It is a multi-layer structure, and each coating includes carbohydrate powder, pyranose compounds, hydroxyl-containing sugars and their derivatives, sodium bicarbonate / borax and deionized water / polymer solution; wherein the mass proportion of the carbohydrate powder is 30-35%, the mass proportion of the pyranose compounds, hydroxyl-containing sugars and their derivatives is 20-35%, and the mass proportion of the sodium bicarbonate / borax is 12-18%.
2. The intumescent anti-laser coating according to claim 1, characterized in that: The thickness of each coating layer is 0.1 mm.
3. The intumescent anti-laser coating according to claim 1, characterized in that: The pyranose compound is α-D-pyranose glucose.
4. The expansion type anti-laser coating according to claim 1, characterized in that: The hydroxyl-containing sugar and its derivatives are sucrose.
5. The intumescent anti-laser coating according to claim 1, characterized in that: The carbohydrate powder is flour, including at least one of wheat flour, corn flour and potato flour.
6. The intumescent anti-laser coating according to claim 1, characterized in that: The bulk density of the coating is no more than 2.6 g / cm 3 .
7. The intumescent anti-laser coating according to claim 1, characterized in that: The mass ratio of the carbohydrate powder, the pyranose compound, the hydroxyl-containing sugar and its derivatives, the sodium bicarbonate / borax and the deionized water / polymer solution is 2:1:1:1:(1-5).
8. A method for preparing an intumescent anti-laser coating as claimed in any one of claims 1 to 7, characterized in that: The method comprises the following steps: Sandblast the substrate to increase its surface roughness; Carbohydrate powder, pyranose compounds, hydroxyl-containing sugars and their derivatives, polyvinyl alcohol / borax and deionized water / polymer solution are mixed according to a set mass ratio, stirred evenly, and a viscous paste is formed; The viscous paste slurry is evenly applied to the surface of the substrate along a preset direction of the substrate, and dried after reaching a first preset thickness; Apply a second layer perpendicular to the first coating direction and dry after reaching a second preset thickness; Repeat the above steps to apply the anti-laser coating vertically and crosswise until the thickness requirement is met.
9. The method for preparing an intumescent anti-laser coating according to claim 8, characterized in that: The first preset thickness is the same as the second preset thickness.
10. The method for preparing an intumescent anti-laser coating according to claim 8, characterized in that: The drying time is 0.5 to 1 hour.
Citation Information
Patent Citations
Composite protective coating resistant to high-energy laser ablation and preparation method thereof
CN113088109A
Laser-markable substrate, and associated manufacturing method
US20120103545A1
Crosslinkable binders for solvent based intumescent coatings
US20170349776A1
coatings
WO2024126494A1
